CGIAR Genebank Accelerator’s submission to the 14th Session of the Ad Hoc Open-ended Working Group to Enhance the Functioning of the Multilateral System of Access and Benefit-sharing (WG-EFMLS 14) - CGIAR Genebank Accelerator (2025)
The CGIAR Genebank Accelerator made this submission in response to paragraph 22(ii) of the Report of the 13th Session of the Ad Hoc Open-ended Working Group to Enhance the Functioning of the Multilateral System of Access and Benefit-sharing (WG-EFMLS 13) inviting written submissions from regions, contracting parties and stakeholders in advance of WG-EFMLS 14. In this submission, we consider five issues that will be addressed at the next meeting, and which have not yet been subject of protracted consideration by the Working Group. Our comments refer to the texts of the revised draft resolution and SMTA that are included in the final report of WG-EFMLS 13.